Examining the Influence of Lecturer Support and Classroom Environment on Mathematical Resilience, Self-Efficacy, and Self-Confidence - Mandailina, Vera (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
This study aims to investigate the relationship between lecturer support, classroom environment, and several student psychological factors such as mathematical resilience, self-efficacy, and self-confidence. The research subjects consisted of 77 mathematics education students. The research instrument was a 38-question questionnaire. The results of data analysis showed that students gave positive responses with an average of 80.03 to lecturer support, 75.66 to the classroom environment, 79.15 to mathematical resilience, 80.57 to self-efficacy, and 75.95 to self-confidence. Furthermore, multiple linear regression analysis showed that lecturer support and classroom environment significantly influenced students' mathematical resilience by 26.7%, self-efficacy by 25.5%, and self-confidence by 30.2%. This finding indicates that the implementation of learning both in the classroom and outside the classroom is considered quite good by students. It also provides a deeper understanding of the factors that contribute to students' learning experience. The implications of this finding suggest developing strategies to improve the quality of learning by taking into account aspects of lecturer support and physical and social environmental conditions. Thus, it is expected to support students' academic achievement and personal development optimally. Keywords: Learning Environments, Lecturer Support, Mathematical Resilience, Self-Efficacy, Self-Confidence